ZPA Regulatory Sequence Variants in Chinese Patients With Preaxial Polydactyly: Genetic and Clinical Characteristics - Zeng, Lei; Jin, Jie-Yuan; Luo, Fang-Mei; Sheng, Yue; Wu, Pan-Feng; Xiang, Rong (Frontiers in Pediatrics, 2022)
Preaxial polydactyly (PPD) is a common congenital abnormality with an incidence of 0.8–1.4% in Asians, characterized by the presence of extra digit(s) on the preaxial side of the hand or foot. PPD is genetically classified into four subtypes, PPD type I–IV. Variants in six genes/loci [including GLI family zinc finger 3 (GLI3), ZPA regulatory sequence (ZRS), and pre-ZRS region] have been identified in PPD cases. Among these loci, ZRS is, perhaps, the most special and well known, but most articles only reported one or a few cases. There is a lack of reports on the ZRS-variant frequency in patients with PPD. In this study, we recruited 167 sporadic or familial cases (including 154 sporadic patients and 13 families) with PPD from Central-South China and identified four ZRS variants in four patients (2.40%, 4/167), including two novel variants (ZRS131A > T/chr7:g.156584439A > T and ZRS474C > G/chr7:g.156584096C > G) and two known variants (ZRS428T > A/chr7:g.156584142T > A and ZRS619C > T/chr7:g.156583951C > T). ZRS131A > T and ZRS428T > A were detected in PPD I cases and ZRS474C > G and ZRS619C > T combinedly acted to cause PPD II. The detectable rate of ZRS variants in PPD I was 1.60% (2/125), while PPD II was significantly higher (9.52%, 2/21). Three bilateral PPD cases harbored ZRS variants (13.64%, 3/22), suggesting that bilateral PPD was more possibly caused by genetic etiologies. This study identified two novel ZRS variants, further confirmed the association between ZRS and PPD I and reported a rare PPD II case resulted from the compound heterozygote of ZRS. This investigation preliminarily evaluated a ZRS variants rate in patients with PPD and described the general picture of PPD in Central-South China.